A conquista do oeste/RBS TV: memória e identidade gaúcha na fronteira oeste brasileira. - Ferreira, Priscila (2012)
This study addresses the memory and identity of Gauchos in the western border of Brazil by analyzing the narrative structure of the documentary series A Conquista do Oeste, produced by RBS TV in 2004. A Conquista do Oeste reconstructs the path of Gauchos who chased their dreams throughout the Brazilian territory. The episodes present the histories, challenges and success of these migrants, who founded cities along the Brazilian border but still managed to develop the customs and traditions they brought from the Rio Grande do Sul state. Thus, the aim of this dissertation is to analyze how the series of documentaries A Conquista do Oeste contributed for the consolidation of a memory project that strengthens the myth around gaucho's image in the western border of Brazil. The methodology used consisted of film analysis, and aesthetics of repetition and fragments, supported by an analysis corpus composed by all 13 episodes of the documentary. The analysis was divided in two moments: first, the analysis of the narrative structure of the series, when was verified how aesthetics of repetition and fragments are constructed as a whole. After that, the idea is to map which elements repeat until they create together the identity of the series. The focus here is to understand implications of using fragments of interviews in order to consolidate the myth around the image of the Gaucho and how they contribute for the construction of three idea-images concerning the migrating Gaucho: the Conqueror, the Explorer and the Hero. As a result, we consider that testimonies from social characters in television narrative fill a memory registry that utilizes the memories as raw-matter for constituting the identity of subjects from a specific social group. The construction of the triarchy Conqueror, Explorer and Hero occurs due to the tone the TV station intended to reaffirm in the series: to portrait the Gaucho migrant s condition of otherness through the opposition for the local culture of the region adopted as a new home.